Dynamic donor-derived cfDNA normalization after kidney transplantation: Preliminary results from a personalized NGS and AI-based monitoring platform - Polat, M. E.; Ceviz, K.; Ergin, B.; Karimzade, K.; Mirioglu, I; Das, B.; Olcucuoglu, E. (Elsevier, 2026)
[Abstract Not Available]